On asymptotic equivalence of solutions of stochastic and ordinary equations - Novak, I. H.; Samoilenko, A. M.; Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
For a weakly nonlinear stochastic system, we construct a system of ordinary differential equations the behavior of solutions of which at infinity is similar to the behavior of solutions of the original stochastic system.